Upaya Sekolah dalam Melibatkan Ayah pada Pendidikan Anak Usia Dini - Nengsih, Zarlia (Tadabbur: Jurnal Peradaban Islam, 2020)
A father has taken very important role in his children's life. The involvement of a father in the life of his child could considerably help his child’s growth in education. Therefore, a father should not put his responsibility in educating children on to his wife’s shoulder (to the mother) only, by having the reason that he is quite busy with his works. Simultaneously, the school has a great opportunity to help the child’s father to be involved in early childhood education. The objective of this study is to analyze the role of the child’s father in early childhood education, its correlation to the school’s programs and its strategies in involving the child’s father in early childhood education in the PAUD of Griya Ceria, and then to find out the constraints experienced by the school in involving the father in early childhood education in this school. This study uses a qualitative method with a descriptive analysis approach. The data was collected through interview techniques, observation, and documentation. The result of the data analysis disclosed: (1) the role of the father in early childhood education in PAUD of Griya Ceria. This includes caring, spending for the living, shaping the intelligence, loving and giving good examples to the child. (2) The PAUD of Griya Ceria has carried out some programs to involve the father in early childhood education. Among them are parenting, art performances, communication with parents, and report card distribution. (3) There are some constraints faced by the school in involving fathers in early childhood education such as the children’s fathers who are busy, the working mothers and the absence of male teachers in the school.